STATUS DAN KEDUDUKAN WALI DALAM PERNIKAHAN TERHADAP ANAK HASIL ZINA MENURUT PERSPEKTIF MADZHAB SYAFI’I DAN KUHPERDATA - Rahman, Arif (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
This study aims to analyze the status and position of guardians in the marriage of children resulting from adultery from the perspective of the Syafi'i School of Law and the Civil Code (KUHPerdata). Marriage is one of the important institutions in Islam, with guardians playing a key role in determining the validity of a marriage. However, the status of children resulting from adultery who are not recognized as legitimate descendants by their biological fathers raises questions about who has the right to be a guardian in the child's marriage. This study uses a qualitative research method with a library research approach, reviewing various literature and related books to understand the position of guardians in the marriage of children resulting from adultery. The results of the study show that according to the Syafi'i School of Law, children resulting from adultery do not have a guardian from the father's lineage, so the judge guardian becomes the legal guardian in their marriage. Meanwhile, in the Civil Code, children resulting from adultery only have a civil relationship with their mother and her family. This analysis highlights the important role of guardians in protecting children's rights and ensuring the validity of marriage, as well as the differences in views between Islamic law and the Civil Code in determining guardians for children resulting from adultery. Thus, this research is expected to provide a more comprehensive understanding of legal protection for children resulting from adultery in the context of marriage.